2020
DOI: 10.3390/brainsci10060379
|View full text |Cite
|
Sign up to set email alerts
|

Early Motor Development Predicts Clinical Outcomes of Siblings at High-Risk for Autism: Insight from an Innovative Motion-Tracking Technology

Abstract: Atypical motor patterns are potential early markers and predictors of later diagnosis of Autism Spectrum Disorder (ASD). This study aimed to investigate the early motor trajectories of infants at high-risk (HR) of ASD through MOVIDEA, a semi-automatic software developed to analyze 2D and 3D videos and provide objective kinematic features of their movements. MOVIDEA was developed within the Italian Network for early detection of Autism Spectrum Disorder (NIDA Network), which is currently coordinating the most e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 75 publications
0
22
0
1
Order By: Relevance
“…The authors found that HR infants later diagnosed with NDD presented higher general motor activity associated with lower variability and velocity, as well as higher acceleration of global movement in the space. Furthermore, these infants showed patterns of higher periodicity of limbs, particularly the upper ones, during the first 12 weeks of life [ 48 ]. Wilson et al utilized in a longitudinal study Opal wearable sensors to assess full day motor activity in five HR infants at 3, 6, 9, 12 months of life, thus obtaining a motion complexity measure.…”
Section: Resultsmentioning
confidence: 99%
“…The authors found that HR infants later diagnosed with NDD presented higher general motor activity associated with lower variability and velocity, as well as higher acceleration of global movement in the space. Furthermore, these infants showed patterns of higher periodicity of limbs, particularly the upper ones, during the first 12 weeks of life [ 48 ]. Wilson et al utilized in a longitudinal study Opal wearable sensors to assess full day motor activity in five HR infants at 3, 6, 9, 12 months of life, thus obtaining a motion complexity measure.…”
Section: Resultsmentioning
confidence: 99%
“…In this scenario, ASD would emerge not as a higher-order social-cognitive deficit, but because of an impairment of the primordial ability to process low level sensory, motor and perceptual information gained through experience with other people since the earliest periods of life [29]. This idea may also be sustained by several studies that reported the presence of early sensorimotor signs in infants/young children with, or at risk of, ASD [30][31][32], and also the presence of a relationship between early motor delay and later communication delay in infants at risk for ASD [33,34]. Unlike the comparison group, the ASD children appeared more likely to have abnormalities across multiple sensory domains, whereas most of the comparison group children had weaker abnormal sensory features.…”
Section: Discussionmentioning
confidence: 97%
“…Since the model including Mullen scores did not explain the data better than the model without this predictor, we do not see evidence that differences in noise in the sensory and motor systems between the two groups influenced their performance on the task. This could be more directly analyzed in future studies by recording motion tracking during the task, a method which has recently shown interesting insights into the development of autism and neurodevelopmental disorders (Achermann et al., 2020 ; Caruso et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%